Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-80999-x
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 blockade enhances anti-tumor immunity via tumor cell intrinsic and extrinsic mechanisms

Abstract: SHP2 is a ubiquitous tyrosine phosphatase involved in regulating both tumor and immune cell signaling. In this study, we discovered a novel immune modulatory function of SHP2. Targeting this protein with allosteric SHP2 inhibitors promoted anti-tumor immunity, including enhancing T cell cytotoxic function and immune-mediated tumor regression. Knockout of SHP2 using CRISPR/Cas9 gene editing showed that targeting SHP2 in cancer cells contributes to this immune response. Inhibition of SHP2 activity augmented tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…Others have reported that SHP2is evoke meaningful anti-tumor T cell responses (5,6). These studies analyzed subcutaneous syngeneic tumors, which lack tissue-specific immunity and display mutational spectra that do not reflect the cognate human malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that SHP2is evoke meaningful anti-tumor T cell responses (5,6). These studies analyzed subcutaneous syngeneic tumors, which lack tissue-specific immunity and display mutational spectra that do not reflect the cognate human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…"Driver" mutations (e.g., amplified or mutant RTKs, mutant KRAS) significantly-and differentially-also have tumor cell-intrinsic and -extrinsic effects and evoke distinct cellular and humoral responses in different tissues (3). Consequently, SHP2is likely have important, potentially driver-specific, effects on the tumor microenvironment (TME), including potentially complex effects on anti-tumor immunity (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators reported that SHP-2 ablation in macrophages potentiated production of CXCL9 in response to IFN-, thereby facilitating tumor infiltration by T cells 110 . Combined approaches of SHP-2 allosteric inhibitors together with pharmacologic RTK inhibitors or KRAS G12C -GDP inhibitors have been employed with the main purpose of targeting signaling vulnerabilities of cancer 108,111,112 . These studies have reported that such treatments, by changing the properties of cancer, also alter immune cells of the TME, including increase of CD8 + T cells, depletion of pro-tumorigenic M2 TAMs via attenuation of Csf1 signaling 109 , increase of M1 TAMs and reduced immunosuppression function of MDSCs 107,108,112 , but the mechanisms remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Combined approaches of SHP-2 allosteric inhibitors together with pharmacologic RTK inhibitors or KRAS G12C -GDP inhibitors have been employed with the main purpose of targeting signaling vulnerabilities of cancer 108,111,112 . These studies have reported that such treatments, by changing the properties of cancer, also alter immune cells of the TME, including increase of CD8 + T cells, depletion of pro-tumorigenic M2 TAMs via attenuation of Csf1 signaling 109 , increase of M1 TAMs and reduced immunosuppression function of MDSCs 107,108,112 , but the mechanisms remained elusive. Our present studies employing a genetic approach to dissect the effects of SHP-2 targeting at multiple levels, showed that myeloid-intrinsic but not T cell-intrinsic depletion of SHP-2 has a dominant anti-tumor effect by altering the myeloid lineage fate, thereby promoting the generation of differentiated granulocytes, and monocytes that became TAMs with signatures of activated antigen presenting cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation